2018
DOI: 10.1007/s11547-018-0910-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose in non-dental cone beam CT applications: a systematic review

Abstract: CBCT of extremities, cervical spine, ears and paranasal sinuses was found to be a low-dose volumetric imaging technique. Effective doses varied significantly because of different exposure settings of CBCT-units and different dosimetry systems used to estimate dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 62 publications
1
23
0
5
Order By: Relevance
“…Clinical studies have shown that implementation of ASIR-V can decrease the mean RD between 34 and 35% while maintaining image quality [13,14]. Previously reported mean RD for low-dose CT evaluation of fractures of the peripheral skeleton has been in the range of 10-800 μSv [12,[15][16][17][18] and for cone-beam CT (CBCT) in the range of 0.9-14.3 μSv [19]. Our ULD-CT protocol has, to our knowledge, the lowest reported mean RD (0.59 μSv) for the peripheral skeleton in the literature, corresponding to around 1.7 h of exposure to background radiation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that implementation of ASIR-V can decrease the mean RD between 34 and 35% while maintaining image quality [13,14]. Previously reported mean RD for low-dose CT evaluation of fractures of the peripheral skeleton has been in the range of 10-800 μSv [12,[15][16][17][18] and for cone-beam CT (CBCT) in the range of 0.9-14.3 μSv [19]. Our ULD-CT protocol has, to our knowledge, the lowest reported mean RD (0.59 μSv) for the peripheral skeleton in the literature, corresponding to around 1.7 h of exposure to background radiation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new three-dimensional imaging technique called cone beam computed tomography (CBCT) has proved to supply an excellent volumetric study of maxillofacial bone structures [10] and satisfactorily recognise mandibular fractures [11]. Moreover, it has a high spatial resolution (0.075-0.4 mm isotropic voxel) [12], delivers relatively low radiation doses compared to MSCT [13], and is only slightly affected by metal artefacts, which often occur in patients stabilised by immobilisation techniques that use metallic materials during post-treatment follow-up [14]. Long scan times (5.4-40 s) [15] advise against the use of CBCT in patients who experience pain and have functional disability for the increased risk of motion artefacts [16].…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Detection of fractures and fracture-related findings in CBCT and radiography is summarized in Table 2 (upper extremity) and Table 3 (lower extremity). Fifty-two patients (56.5%) received surgical therapy after imaging (44 upper/8 lower extremities), with the majority of surgical procedures (34) comprising open reduction and internal fixation of distal forearm fractures. Thirty-four patients (37.0%) were treated solely with immobilization or functional therapy (27/7).…”
Section: Resultsmentioning
confidence: 99%